(3GdCUhd aj TQM GdaUhds - (3jYbhH Hf ESMGb GdeSjMj Gdedcj GdcQcj GHf Gdba, CHh GdaQL,J (B685 (3g` s
(3ChdgG (B:s
(3hHYO (B: (3SCdfi HYV ef jTGZd Ydi Cf CTQM dg cJGH GdaUhd s
(3BNQgG (B:s
(3hdeG cGf MGdjkG cPdc UGQ NQhLgG eWdbkG ef ahb hCSad YdGeI QOjI egdcI s
(3TQM ajg aUhd CHbQGWs
(3hQJHi Ydi CQHYI hYTQjf aUdkGs
(3UaMGJg GdCNjQI eWehSI GdJUhjQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdChd (B- (3U (B15 s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdWHs